Image Retrieval System with Interactive Genetic Algorithm Using Distance - Mamta R, Nagpure; Suchita S, Mesakar; R Raut, Sonali; P Lonkar, Vanita (International Journal of Computer Sciences and Engineering, 2014)
Digital images have produced a large amount of image data in various areas, such as entertainment, fashion design, education, graphics, medicine, industry, etc. However in order to effectively retrieve the desired images from a large image database, a content-based image retrieval (CBIR) system has become an important research issue to be developed. As no. of the proposed approaches emphasize on finding the best representation for different image features. Because of that a user-oriented mechanism for CBIR method based on an interactive genetic algorithm (IGA) is developed. Color, texture and edge features of an image are extracted quickly using content-based image retrieval (CBIR) system with IGA. The mean value, the standard deviation, and the image bitmap of a color image are used as the features for retrieval. In addition to that entropy based on the gray level co-occurrence matrix and the edge histogram of an image is also considered. The experiments show that the method developed is very fast and retrieval performance achieved 100%.